2022
DOI: 10.1097/cce.0000000000000604
|View full text |Cite
|
Sign up to set email alerts
|

Out-of-the-ICU Mobilization in Critically Ill Patients: The Safety of a New Model of Rehabilitation

Abstract: OBJECTIVES: Early mobilization of ICU patients has been reported to be safe and feasible. Recently, our ICU implemented out-of-the-ICU wheelchair excursions as a daily rehabilitation practice. The aim of this study is to investigate the safety of participation in the out-of-the-ICU program for early mobilization. DESIGN: Retrospective cohort study. SETTING: Single general ICU in a tertiary teaching hospital. PATIENTS: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
1
0
2
Order By: Relevance
“… 14 Human interactions especially with family members in a pleasurable outdoor activity, as in this case, appear to be beneficial for cognitive stimulation, reorientation, a sense of normalcy, and reassurance to patients during their ICU stay, since contact isolation has been associated with depression and anxiety. 21 We have reported the safety of out‐of‐the‐ICU mobilization 22 and show evidence suggesting that out‐of‐the‐ICU activities contributed to this critically ill patient's psychological orientation and his family's motivation to undertake a long course of rehabilitation. Numerous reports have shown that subsequent post‐acute rehabilitation programs need to be established in a holistic and seamless manner to support COVID‐19 survivors.…”
Section: Discussionmentioning
confidence: 91%
“… 14 Human interactions especially with family members in a pleasurable outdoor activity, as in this case, appear to be beneficial for cognitive stimulation, reorientation, a sense of normalcy, and reassurance to patients during their ICU stay, since contact isolation has been associated with depression and anxiety. 21 We have reported the safety of out‐of‐the‐ICU mobilization 22 and show evidence suggesting that out‐of‐the‐ICU activities contributed to this critically ill patient's psychological orientation and his family's motivation to undertake a long course of rehabilitation. Numerous reports have shown that subsequent post‐acute rehabilitation programs need to be established in a holistic and seamless manner to support COVID‐19 survivors.…”
Section: Discussionmentioning
confidence: 91%
“…Ressalta-se que a presença de um quantitativo profissional treinado no turno da manhã e de um contingente escalado para a tarde permite uma melhor atuação para com a prática de MP, favorecendo a aplicação continuada dos protocolos e obtendo resultados satisfatórios 10,11 .…”
Section: Discussionunclassified
“…Tais informações concordam com a presente pesquisa, na qual 80% dos entrevistados, a grande maioria, conhece a MP e suas funções nesse método enquanto profissionais; 62,82% afirmaram redução no tempo de ventilação mecânica; e 64,10%, aumento da força muscular periférica. A interação multiprofissional é essencial na abordagem da MP, de forma a potencializar a eficácia e o benefício do tratamento, minimizando o surgimento de complicações, diminuindo o tempo de internação, custos hospitalares e acelerando o retorno do paciente ao convívio familiar e social 11 . Em adultos, a MP está associada com desfechos positivos em curto e longo prazo, como melhora da força muscular periférica 12,13 .…”
Section: Discussionunclassified